A Highly Selective and Sensitive Fluorescent Probe With a Large Stokes Shift for Near-Infrared Visualization of Endogenous and Exogenous Biothiols in Living Cells - Xiaomin Li; Rongrong Yuan; Yangmin Ma; Guanglong Li; Siyue Ma (Frontiers in Bioscience-Landmark)
Background: Fluorescent probes have become a powerful tool for monitoring biothiol concentrations, aiding in disease diagnosis and treatment while also facilitating the exploration of fundamental biological processes. However, the probes are limited by the short fluorescence emission wavelength and small Stokes shift, which makes them susceptible to background fluorescence interference and significant self-absorption. To overcome these limitations and achieve high-fidelity biothiols detection in complex biological systems, this study focuses on developing a near-infrared fluorescent probe with an extended Stokes shift. Methods: (E)-4-(5-(2-(4-(dicyanomethylene)-4H-chromen-2-yl)vinyl)thiophen-2-yl)phenyl 2,4-dinitrobenzenesulfonate (DCMOS-N), a near-infrared (NIR) fluorescent probe featuring a large Stokes shift, was designed and synthesized for biothiols detection. The optical properties of DCMOS-N were evaluated using ultraviolet-visible (UV-Vis) and fluorescence spectroscopy. Additionally, its imaging capabilities for detecting biothiols in living cells were assessed through confocal fluorescence microscopy. Results: Fluorescence spectral analysis confirmed that the DCMOS-N probe exhibits high selectivity and strong anti-interference properties in biothiol detection. Moreover, its fluorescence intensity increases upon the addition of biothiols. Notably, a strong linear correlation was observed across the concentration range of 0 to 100 μmol/L (R2 = 0.9944 for glutathione (GSH), 0.9942 for cysteine (Cys), and 0.9946 for homocysteine (Hcy)), enabling the quantitative analysis of biothiol concentrations in biological systems. The detection limits for GSH, Cys, and Hcy were determined as 0.142 μmol/L, 0.129 μmol/L, and 0.143 μmol/L, respectively. Importantly, the practical application of DCMOS-N in living cells was validated, with confocal fluorescence imaging demonstrating its capability to detect both endogenous and exogenous biothiols in HeLa cells. Conclusion: An NIR fluorescent probe, DCMOS-N, was developed and effectively utilized to monitor biothiols in living HeLa cells. The successful design of DCMOS-N presents significant potential and serves as an innovative platform for developing fluorescence probes targeted at biothiols.